Forms and Functions of Speech Communication in F. M. Dostoevsky’s Demons - Svetlana V. Rudakova; Tatyana B. Zaitseva; Alexandr P. Vlaskin (СибСкрипт, 2024)
Fyodor Dostoevsky’s novels resonate with the vibes of the current epoch: the fundamental issues that his personages tried to fathom are as relevant now as they were in the XIX century. The problem of communication is one of such issues: oral verbal interaction between people is one of the most disputed problems in modern humanities. The authors relied on the systematic approach, as well as on hermeneutical, analytical, and statistical methods, to analyze the peculiarities of verbal communication in F. M. Dostoevsky’s Demons. The analysis covered the way the author introduced the main characters (Daria Shatova, Pyotr Verkhovensky, Stavrogin, Lebyadkin, Marya Lebyadkina, Kirillov) through their speech and made it possible to build their speech profiles. As for the forms and functions of speech communication, the authors believe that F. M. Dostoevsky understood the need for human communication as fundamental and urgent. The writer tested his personages for this need: it was through interpersonal communication that Dostoevsky’s characters manifested their existence and attitudes.